Élmu palak: Ethnomathematics exploration in mathematics at Sukabumi district high school - Rineka Rosinansis; Novi Andri Nurcahyono; Hamidah Suryani Lukman (Journal of Advanced Sciences and Mathematics Education, 2022)
This study examines the arithmetic used by Sundanese people, especially in several regions in Sukabumi Regency, as a cultural heritage that can be used for activities in daily life using specific patterns. Some traditional societies in the Sunda region are still closely related to the beliefs adopted and passed down from their ancestors. This study aims to determine the mathematical material in the élmu palak count, especially in repok countinging pattern (match count of matchmaking before marriage). The method used in this study is the ethnographic method with a qualitative approach and a gradually advanced research flow. The subjects used in this study are limited to five people from different sub-districts determined using purposive sampling technique. The study found that there are a variety of counting patterns, but in general, the calculation elements consist of the name and/or day of birth. Other than that, there is relevance to high school mathematics material, one of which is the material relations and functions, residual theorem, and modulo.